Bite Force Simulator: A Novel Technique to Simulate Craniofacial Strain In Vitro. Issue 3 (May 2020) - Ip, Kenneth K.C.; You, Peng; Moore, Corey C.; Ferreira, Louis M.
Abstract : Abstract: Existing in vitro simulators rely on external manipulation of the skull to replicate masticatory forces; however, external manipulations do not accurately represent internal loads as in physiological muscle forces. The purpose of the project is to develop an in vitro simulator that internally replicates the forces of mastication. The simulator has 3-dimensional-printed piston mounts that are reverse-engineered using a computed tomography scan of the specimen. The mounts are attached to the skull at muscle attachment sites using adhesive. The pneumatic pistons are sutured to muscle tendons; when the pistons are activated, they pull on the tendons which proportionally replicate muscle loads. The force output of the pistons can be individually modified by a custom software. Strain gauges are attached to craniofacial bones to measure deformation under replicated muscle loads. A 6 degrees-of freedom force sensor is placed intraorally to measure the generated bite force. The methodology was validated on 6 fresh-frozen cadaveric heads. Change in strain measurements was observed with change in simulated muscle loads. The simulator can validate computer simulation models and provide an experimental platform for craniofacial and dental implants. It sets the framework for a new, more physiologically consistent way of studying craniofacial stresses. Abstract : Supplemental Digital Content is available in the text